Ventilator-associated tracheobronchitis: pre-emptive, appropriate antibiotic therapy recommended - Craven, Donald E (Crit Care, 2014)
Nseir and colleagues presented data from a large multicenter study of patients with ventilator-associated tracheobronchitis (VAT), demonstrating that appropriate antibiotic therapy for VAT was an independent predictor for reducing transition to pneumonia (ventilator-associated pneumonia, or VAP). These data added to the growing evidence supporting the use of appropriate antibiotic therapy for VAT as a standard of care to prevent VAP and improve patient outcomes.